009 Axonal excitability properties in dravet's syndrome reflect effect of loss of sodium channels. (29th July 2019) - Farrar, Michelle A; Tomlinson, Susan E; Howells, James; Lin, Cindy Shin-YI; Carey, Kate; Park, Susanna B; Hollingsworth, Georgina; Lawson, John A; Kiernan, Matthew C; Berkovic, Sam F; Burke, David; Scheffer, Ingrid E
Abstract : Introduction: Mutations in SCN1A encoding the Nav 1.1 subunit of the neuronal sodium channel underlie the devastating epilepsy of Dravet's syndrome. 1 The mechanism by which Nav 1.1 dysfunction causes seizures is not clear. In vitro and in silico channel evaluation can support mutation pathogenicity but cannot define the in vivo impact of channel dysfunction. Axonal excitability studies can show the pattern of single-channel dysfunction in disorders where the channel is peripherally expressed. 2 This study was undertaken to determine whether axonal excitability studies could detect changes in Dravet's patients related to the condition or due to medication effect. Methods: Patients with Dravet's syndrome were recruited from clinics in Sydney and Melbourne and axonal excitability studies were performed. Excitability results were analysed in 3 age groups and compared to age-matched normal controls. Results: Twenty six patients (ages 2–46) were studied. Findings were most pronounced in patients aged 20–46 (n=7) with 6.9% greater increase in threshold during hyperpolarization(p=0.1), 7.6% greater threshold decrease on depolarization(p=0.005) and, in the recovery cycle, 19.7% reduction in superexcitability(p=0.002) and 26% reduction in subexcitability(p=0.03). Axonal excitability studies resembled previously published changes seen in patients with sodium channel blockade caused by acute tetrodotoxin poisoning. 3 Conclusions: Changes in excitability of axonal membrane in Dravet's syndrome are consistent with a decrease in sodium channel function. As the affected channel in Dravet's syndrome is not peripherally expressed, the effect seen is likely due to the heavy anticonvulsant regime required to control epilepsy, combined with a progressive loss of sodium channel function that occurs with age. References: Meisler MH, O'Brien JE, Sharkey LM. Sodium channel gene family: epilepsy mutations, gene interactions and modifier effects. J Physiol 2010;588:1841–1848. Tomlinson SE, Howells J, Burke D. In vivo assessment of neurological channelopathies: Application of peripheral nerve excitability studies. Neuropharmacology . 2018 Apr;132:98–107. Kiernan MC, Isbister GK, Lin CS, Burke D, Bostock H. Acute tetrodotoxin-induced neurotoxicity after ingestion of puffer fish. Ann Neurol 2005;57:339–48.